Acute surgical unit improves outcomes in appendicectomy. Issue 9 (15th April 2019) - Kinnear, Ned; Bramwell, Eliza; Frazzetto, Alannah; Noll, Amy; Patel, Prajay; Hennessey, Derek; Otto, Greg; Dobbins, Christopher; Sammour, Tarik; Moore, James
Abstract : Background: Few large Australian studies have explored the impact of acute surgical unit (ASU) model in appendicitis. Methods: An ASU model commenced practice at our institution on 1 August 2012. In this retrospective cohort study, patients undergoing appendicectomy 2.5 years before (Traditional group) or after (ASU group) this date were compared. Primary outcomes were median length of stay, median time from emergency department referral to theatre start and proportion of cases performed in‐hours. Secondary outcomes were rates of complications, open appendicectomy, consultant scrubbed for procedure, intensive care unit admission and re‐presentation to emergency department within 30 days. Results: After removing those with incomplete data, 1214 patients were enrolled; 465 in the Traditional group and 749 in the ASU group. There were no significant baseline differences between groups. Compared with the Traditional group, ASU patients had similar length of stay (1.81 versus 1.81 days; P = 0.54) and time to theatre (0.59 versus 0.56 days; P = 0.14), but a greater proportion of in‐hours operation (72% versus 79%; P = 0.014). The ASU group also experienced fewer complications (9% versus 6%; P = 0.031), fewer primary open (4% versus 1%; P < 0.0001) or conversion‐to‐open appendicectomies (6% versus 2%; P < 0.0005) and had superior rates of consultant scrubbed in theatre (21% versus 56%; P < 0.00001). Rates of intensive care unit admission (1% versus 1%; P = 0.72) and re‐presentation were unchanged (5% versus 5%; P = 0.46). Conclusion: In our institution, the introduction of an ASU model was associated with more in‐hours operations and safer care for patients undergoing appendicectomy. Abstract : The acute surgical unit dedicates an on‐site registrar, an on‐call consultant and an operating theatre to the task of managing emergency general surgery presentations, 24 h/day. In this single‐centre retrospective cohort study of 1214 patients undergoing appendicectomy, compared with the prior Traditional model, the acute surgical unit model was associated with more daytime operating, fewer complications and fewer open procedures.